PENINGKATAN KEMAMPUAN MICROSOFT OFFICE PADA SISWA KELAS V DI SD NEGERI MUKTIHARJO KIDUL 01 SEMARANG - Ahmad Rifa'i; Vensy Vydia; Tirta Jurista Kumkandani (TEMATIK, 2019)
Microsoft Office is a basic capability that everyone must have. This is evidenced by the use of Microsoft Office in the world of education, offices, and everyday life. In the world of education Microsoft office has been introduced starting from elementary level education. The teacher gives school assignments also using Microsoft Office, for example the teacher gives assignments to students to make articles. In completing this school assignment, students will usually ask for help from an internet cafe operator or brother to help do it. Students of Muktiharjo Kidul 01 Elementary School Semarang have not all been able to master the Microsoft Office application.The purpose of this service is to use Microsoft Office to do school assignments related to making articles and others. The output of this service is that participants are able to make their own school assignments using Microsoft Office.